Morfologia da semente e desenvolvimento pós-seminal em cinco espécies de bromeliaceae - Stefanini, Lorraine [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The aim of this study was to describe the morphology and the stages of germination of Aechmea blanchetiana (Baker) L.B.Sm. Aechmea bromeliifolia (Rudge) Baker, Neoregelia marmorata (Baker) L.B.Sm., Pitcairnia flammea Lindl. e Vriesea incurvata Gaudich. The species have epigeal and cryptocotylar germination, with different periods and germination rates. The embryos have axial position with short and cylindrical embryonic axes, the endosperm containing starch and the tegument has overlapping cells. The radicle shows ring- shaped pilosity before the issuance. The seeds of Aechmea and Neoregelia (Bromelioideae) presents mucilage that prevents drying out, Pitcairnia L'Hér. (Pitcairnioideae) has seeds with membranous wings and in Vriesea Lindl. (Tillandsioideae) the seeds show feathery appendages. In A. blanchetiana, A. bromeliifolia, N. marmorata (Bromelioideae) and Pitcairnia flammea (Pitcairnioideae) the post-seminal development starts with the emergence of primary root; to Vriesea incurvata (Tillandsioideae) we observed a haustorial cotyledon. The results obtained in this study are basis in the area of seed technology involving these species, as well as the taxonomy of Bromeliaceae

O objetivo do presente trabalho foi descrever a morfologia da semente e as etapas do processo germinativo de Aechmea blanchetiana (Baker) L.B.Sm. Aechmea bromeliifolia (Rudge) Baker, Neoregelia marmorata (Baker) L.B.Sm., Pitcairnia flammea Lindl. e Vriesea incurvata Gaudich. As espécies apresentaram germinação epígea e criptocotiledonar, diferindo entre si nos períodos e porcentagem de germinação. Os embriões possuem posição axial com eixos embrionários curtos e cilíndricos, o endosperma contém células de amido e o tegumento é composto por células justapostas. Antes da emissão da raiz primária observa-se pilosidade em forma de anel na radícula. O envoltório das sementes de Aechmea Ruiz & Pav. e Neoregelia L.B.Sm. (Bromelioideae) apresenta mucilagem que evita a dessecação; enquanto que em Pitcairnia L’Hér. (Pitcairnioideae) as sementes apresentam alas membranáceas e em Vriesea Lindl. (Tillandsioideae) notam-se apêndices plumosos. O início do desenvolvimento pós-seminal de A. blanchetiana, A. bromeliifolia, N. marmorata (Bromelioideae) e Pitcairnia flammea (Pitcairnioideae) é marcado pela emergência da raiz primária, já em Vriesea incurvata (Tillandsioideae) observa-se a emergência do cotilédone haustorial.Os resultados obtidos no presente estudo subsidia a área de tecnologia de sementes envolvendo as espécies estudadas, assim como a taxonomia de Bromeliaceae
Keywords: Bromeliacea; Angiosperma; Germinação; Botânica - Morfologia; Anatomia vegetal; Sementes; Germination